2021
DOI: 10.3390/app11167685
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Prediction through Sensing Using Hidden Markov Models—A Case Study

Abstract: The availability maximization is a goal for any organization because the equipment downtime implies high non-production costs and, additionally, the abnormal stopping and restarting usually imply loss of product’s quality. In this way, a method for predicting the equipment’s health state is vital to maintain the production flow as well as to plan maintenance intervention strategies. This paper presents a maintenance prediction approach based on sensing data managed by Hidden Markov Models (HMM). To do so, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Zhang et al [46] proposed an approach to perform a prognosis of rotating equipment's health using wavelet transform (WT), a principal component analysis (PCA) and artificial neural networks (ANN) to classify the failure and predict the condition of components, equipment and machines. Martins et al [47] showed how it was possible to classify the health condition of equipment via an HMM with multivariate analysis. Yu [48] proposed an adaptive HMM method that evolved over time to detect equipment failures and component degradation monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang et al [46] proposed an approach to perform a prognosis of rotating equipment's health using wavelet transform (WT), a principal component analysis (PCA) and artificial neural networks (ANN) to classify the failure and predict the condition of components, equipment and machines. Martins et al [47] showed how it was possible to classify the health condition of equipment via an HMM with multivariate analysis. Yu [48] proposed an adaptive HMM method that evolved over time to detect equipment failures and component degradation monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…Monitoring the condition of engine oil, understood as a type of preventive maintenance, allows fleet managers to make appropriate decisions before a failure occurs based on the data obtained, their detailed analysis using computer tools, and the detection of change trends [23][24][25][26]. Laboratory methods allow for obtaining detailed information on the physico-chemical properties of lubricating oil.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing technologies like Neural Networks for modeling pavement performance in order to improve sustainability [15], companies basically expect to have the highest production while utilizing the fewest resources. For this to happen, it is important that assets have predictive maintenance policies to increase their availability [16][17][18][19].…”
Section: Introduction 1frameworkmentioning
confidence: 99%